INVESTIGASI FAKTOR PENENTU FINANCIAL DISTRESS - Sahrul Ponto; Fajar Rina Sejati; Dian Pertiwi; Awaluddin (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2022)
This research was conducted to investigated the factors determine of Financial Distress in Property & Real Estate Sub-Sector Companies. The sample are 11 companies was met the criteria. The analysis technique used is multiple linear regression. The results of the study show that liquidity, sales growth, and institutional ownership has no effect on financial distress. Then, leverage and profitability has a negative and significant effect on financial distress.